Trinitas dalam Perspektif Kaum Unitarian dan Al-Qur’an - Ahmad Ridho; Hafizzatul Nofyn (Inklusiva: Jurnal Studi Agama-Agama, 2025)
This study examines how the Qur’an and unitary sect views the dogma of the trinity (tatslits). The dogma of the trinity is one of the main dogmas that are closely related to the faith of Christians. In this study, it will be studied how the Qur’an will discuss this, namely by referring to the verses that explain the belief that Allah is one of the three (tsalitsu tsalatsa) also accompanied by quoting the opinions of commentators and experts qualified theology in this regard. As well as analyzing some of the opinions of the sects in Christianity as a comparison material regarding this dogma. This study uses a qualitative method with a comparative approach and is expected to provide a response to the treasures of knowledge for the future.